2010
DOI: 10.1073/pnas.1016020107
|View full text |Cite
|
Sign up to set email alerts
|

A single-molecule characterization of p53 search on DNA

Abstract: The tumor suppressor p53 slides along DNA while searching for its cognate site. Central to this process is the basic C-terminal domain, whose regulatory role and its coordination with the core DNAbinding domain is highly debated. Here we use single-molecule techniques to characterize the search process and disentangle the roles played by these two DNA-binding domains in the search process. We demonstrate that the C-terminal domain is capable of rapid translocation, while the core domain is unable to slide and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

23
301
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 222 publications
(329 citation statements)
references
References 36 publications
(54 reference statements)
23
301
2
Order By: Relevance
“…Acetylation of Lys120 is now seen to increase the specificity of p53 and change its conformational preferences. If the data in vitro extend to the situation in vivo, then p53 prior to acetylation of Lys120 would not be in a search process for its targets, but would bind to any exposed nonspecific sequences, possibly sliding along them (35). Acetylation would then start the search process by weakening the binding to nonspecific sequences.…”
Section: Binomial Distribution Experimentalmentioning
confidence: 99%
“…Acetylation of Lys120 is now seen to increase the specificity of p53 and change its conformational preferences. If the data in vitro extend to the situation in vivo, then p53 prior to acetylation of Lys120 would not be in a search process for its targets, but would bind to any exposed nonspecific sequences, possibly sliding along them (35). Acetylation would then start the search process by weakening the binding to nonspecific sequences.…”
Section: Binomial Distribution Experimentalmentioning
confidence: 99%
“…In response to various stress stimuli, p53 acts as a transcriptional activator that specifically binds consensus response elements (REs; two 10-base-pair half-sites [RRRCWWGYYY]) within its target genes to directly stimulate gene expression (2). p53 utilizes its ability to nonspecifically bind and slide along the DNA to expedite the search for target REs (3). Upon recognition of its response genes, p53 facilitates transcription at least in part by targeting the TFIID-mediated transcription machinery to the promoter (4)(5)(6)(7).…”
mentioning
confidence: 99%
“…Recent single-molecule experiments revealed that the diffusion coefficients for 1D sliding along DNA are two or more orders of magnitude lower than the 3D diffusion coefficients [20,21,[51][52][53]. Previously it was often assumed that for reaction acceleration by reduction of dimensionality to occur, the 1D diffusion coefficients have to be higher or of the same order of magnitude as the related 3D diffusion coefficients [54].…”
Section: Numerical Simulation and Discussionmentioning
confidence: 99%